Dimeric dipeptide mimetic the 1st loop of nerve growth factor of GK-6, which activates PI3K/AKT and MEK/MAPK/ERK, causes a neuronal type differentiation of PC12 cells - T. A. Antipova; S. V. Nikolaev; A. V. Revishchin; E. A. Savchenko; G. V. Pavlova; T. A. Gudasheva (Фармакокинетика и Фармакодинамика)
Dimeric dipeptide mimetic 1st loop of NGF GK-6 (10-6M) activating as phosphatidylinozitol 3-kinase/Akt and mitogen-activated protein kinase MEK/MAPK/ERK) signaling cascades causes PC12 cell differentiation into neuron-like cells. At the same time dimeric dipeptide mimetic the 4th loop of NGF GK-2 (10-6M), which activates only phosphatidylinozitol 3-kinase/Akt, does not possess the differentiating effect.